2014
DOI: 10.3109/13880209.2014.911331
|View full text |Cite
|
Sign up to set email alerts
|

Chemical identification and evaluation of the antimicrobial activity of fixed oil extracted fromRhinella jimi

Abstract: Objectives: The present work examined the antimicrobial actions of the extracted oils from the body fat of R. jimi (ORJ) against fungi and standard and multi-resistant lines of bacteria, as well as their effects when combined with aminoglycosides. Materials and methods: The toads were collected in the municipality of Exu in Pernambuco State, Brazil, and their body fat oils extracted in a Soxhlet apparatus using hexane. A gas chromatograph coupled to a mass spectrometer was used to identify the fatty acids, bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The fixed “pequi” oil, for example, potentiated the activity of gentamicin, kanamycin, amikacin, and neomycin in a range of 87.5 to 99.8% against S. aureus standard and multiresistant strains [2]. The Rhinella jimi , an amphibian, fixed skin oil significantly enhanced the antibiotic activity against multiresistant E. coli when associated with amikacin [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fixed “pequi” oil, for example, potentiated the activity of gentamicin, kanamycin, amikacin, and neomycin in a range of 87.5 to 99.8% against S. aureus standard and multiresistant strains [2]. The Rhinella jimi , an amphibian, fixed skin oil significantly enhanced the antibiotic activity against multiresistant E. coli when associated with amikacin [5].…”
Section: Resultsmentioning
confidence: 99%
“…Due to aminoglycoside resistance, many plants have been studied not just for their antibacterial activity, but also for their modifying action. Natural plant products can alter antibiotic effects by improving or decreasing their activity such that these products can be a viable alternative for the resistance issue [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with species belonging to the Rhinella genus have identified the presence of different saturated fatty acids, including lauric acid, myristic acid, pentadecanoic acid, stearic acid, palmitic acid and heptadecanoic acid, and of unsaturated fatty acids, including arachidonic acid, linoleic acid, oleic acid and palmitolytic acid, in fixed oils obtained from the body fat of Rhinella jimi frogs (Stevaux 2002) (Sales et al 2015).…”
Section: Zoopharmacognosy and Zoopharmacology In The Caatingamentioning
confidence: 99%
“…Of the 150 prescription drugs currently in use in the United States of America, 27 have animal origin (World Resources Institute, 2000). Although the potential of faunal biodiversity is well known, a Thammasirirak et al (2006) Amyda cartilaginea (Boddaert, 1770) Antibacterial Thammasirirak et al (2006) Chelonia mydas (Linnaeus, 1758) Antibacterial Thammasirirak et al (2006) Nasutitermes corniger (Motschulsky, 1855) Modulation of the antibiotic activity Coutinho et al (2009Coutinho et al ( , 2010 and Chaves et al (2014) Atta sexdens rubropilosa (Forel, 1908) Antifungal Masaro et al (2001) Squalus acanthias (Linnaeus, 1758) Antibacterial Donia and Hamann (2003) Leptodactylus macrosternum (Miranda-Ribeiro, 1926) Antibacterial Cabral et al (2013) Leptodactylus vastus (Adolf Lutz, 1930) Antibacterial Cabral et al (2013) Pseudocanthotermes spiniger Antibacterial and antifungal Lamberty et al (2001) Gallus gallus domesticus (Linnaeus, 1758) Modulation of the antibiotic activity Coutinho et al (2014) Rhinella jimi (Stevaux, 2002) Modulation of the antibiotic activity Sales et al (2015) Rhynocoris marginatus (Fabricius, 1794) Antibacterial Sahayaraj et al (2006) Catamirus brevipennis (Servile) Antibacterial Sahayaraj et al (2006) Tropidurus hispidus (Spix, 1825) Modulation of the antibiotic activity; antiinflammatory Santos et al (2012Santos et al ( , 2015 Tropidurus Naja atra (Cantor, 1842) Antiinflammatory Zhu et al (2016) careful strategy is required if species are to be exploited sustainably. One of the main conservation concerns about the exploitation of fauna in the search for bioactive compounds is the possible overharvesting of target organisms (Alves and Albuquerque, 2013).…”
Section: Fauna As Source Of Drugsmentioning
confidence: 99%